Bimodal EEG-fNIRS in Neuroergonomics. Current Evidence and Prospects for Future Research - Bourguignon, Nicolas J.; Bue, Salvatore Lo; Guerrero-Mosquera, Carlos; Borragán, Guillermo (Frontiers in Neuroergonomics, 2022)
Neuroergonomics focuses on the brain signatures and associated mental states underlying behavior to design human-machine interfaces enhancing performance in the cognitive and physical domains. Brain imaging techniques such as functional near-infrared spectroscopy (fNIRS) and electroencephalography (EEG) have been considered key methods for achieving this goal. Recent research stresses the value of combining EEG and fNIRS in improving these interface system’s mental state decoding abilities, but little is known whether these improvements generalize over different paradigms and methodologies, nor about the potentialities for using these systems in the real world. We present a systematic review of 33 studies comparing mental state decoding accuracy between bimodal EEG-fNIRS and unimodal EEG and fNIRS in several subdomains of neuroergonomics. We also consider the remaining challenges towards exploiting wearable versions of these systems in the real world. Our results indicate that bimodal EEG-fNIRS outperforms unimodal EEG or fNIRS despite a limited number of methodologically very different studies. Much work however remains to be done to reach practical applications of bimodal EEG-fNIRS in naturalistic conditions. We consider these points to identify aspects of bimodal EEG-fNIRS research in which progress is expected or desired.